Safety of live vaccinations on immunosuppressive therapy in patients with immune-mediated inflammatory diseases, solid organ transplantation or after bone-marrow transplantation – A systematic review of randomized trials, observational studies and case reports - Croce, Evelina; Hatz, Christoph; Jonker, Emile F.; Visser, L.G.; Jaeger, Veronika K.; Bühler, Silja (Vaccine, 2017)
Live vaccines are generally contraindicated on immunosuppressive therapy due to safety concerns. However, data are limited to corroborate this practice. To estimate the safety of live vaccinations in patients with immune-mediated inflammatory diseases (IMID) or solid organ transplantation (SOT) on immunosuppressive treatment and in patients after bone-marrow transplantation (BMT). A search was conducted in electronic databases (Cochrane, Pubmed, Embase) and additional literature was identified by targeted searches. Randomized trials, observational studies and case reports. Patients with IMID or SOT on immunosuppressive treatment and BMT patients <2years after transplantation. Live vaccinations: mumps, measles, rubella (MMR), yellow fever (YF), varicella vaccine (VV), herpes zoster (HZ), oral typhoid, oral polio, rotavirus, Bacillus Calmette–Guérin (BCG), smallpox. One author performed the data extraction using predefined data fields. It was cross-checked by two other authors. 7305 articles were identified and 64 articles were included: 40 on IMID, 16 on SOT and 8 on BMT patients. In most studies, the administration of live vaccines was safe. However, some serious vaccine-related adverse events occurred. 32 participants developed an infection with the vaccine strain; in most cases the infection was mild. However, in two patients fatal infections were reported: a patient with RA/SLE overlap who started MTX/dexamethasone treatment four days after the YFV developed a yellow fever vaccine-associated viscerotropic disease (YEL-AVD) and died. The particular vaccine lot was found to be associated with a more than 20 times risk of YEL-AVD. One infant whose mother was under infliximab treatment during pregnancy received the BCG vaccine at the age of three months and developed disseminated BCG infection and died. An immunogenicity assessment was performed in 43 studies. In most cases the patients developed satisfactory seroprotection rates. In the IMID group, YFV and VV demonstrated high seroconversion rates. MTX and tumor necrosis factor inhibitory therapy appeared to reduce immune responses to VV and HZ vaccine, but not to MMR and YF-revaccination. Seroconversion in SOT and BMT patients showed mostly higher rates for rubella than for measles, mumps and varicella. Risk of bias was high in the majority of studies since 39 of them were observational and 17 were case series/case reports. Only eight studies were randomized trials. BMT patient numbers included in this review were low. Although live vaccinations were safe and sufficiently immunogenic in most studies, some serious reactions and vaccine-related infections were reported in immunosuppressed IMID and SOT patients. Apart from mild vaccine-related infections MMR and VV vaccines were safe when administered less than two years after BMT. Until further data are available, live vaccinations under most immunosuppressive treatments should only be administered after a careful risk benefit assessment of medications and dosages. None.